Three-dimensional facial swelling evaluation of pre-operative single-dose of prednisone in third molar surgery: a split-mouth randomized controlled trial - Alessandro Antonelli; Selene Barone; Francesco Bennardo; Amerigo Giudice (BMC, 2023)
Abstract Background Facial swelling, pain, and trismus are the most common postoperative sequelae after mandibular third molar (M3M) surgery. Corticosteroids are the most used drugs to reduce the severity of inflammatory symptoms after M3M surgery. This study aimed to evaluate the effect of a single pre-operative dose of prednisone on pain, trismus, and swelling after M3M surgery. Methods This study was designed as a split-mouth randomized, controlled, triple-blind trial with two treatment groups, prednisone (PG) and control (CG). All the parameters were assessed before the extraction (T0), two days (T1), and seven days after surgery (T2). Three-dimensional evaluation of facial swelling was performed with Bellus 3D Face App. A visual analogue scale (VAS) was used to assess pain. The maximum incisal distance was recorded with a calibrated rule to evaluate the trismus. The Shapiro-Wilk test was used to evaluate the normal distribution of each variable. To compare the two study groups, the analysis of variance was performed using a two-tailed Student t-test for normal distributions. The level of significance was set at a = 0.05. Statistical analysis was conducted using the software STATA (STATA 11, StataCorp, College Station, TX). Results Thirty-two patients were recruited with a mean age of 23.6 ± 3.7 years, with a male-to-female ratio of 1:3. A total of 64 M3Ms (32 right and 32 left) were randomly assigned to PG or CG. Surgery time recorded a mean value of 15.6 ± 3.7 min, without statistically significant difference between the groups. At T1, PG showed a significantly lower facial swelling compared to CG (PG: 3.3 ± 2.1 mm; CG: 4.2 ± 1.7 mm; p = 0.02). Similar results were recorded comparing the groups one week after surgery (PG: 1.2 ± 1.2; CG: 2.1 ± 1.3; p = 0.0005). All patients reported a decrease in facial swelling from T1 to T2 without differences between the two groups. At T1, the maximum buccal opening was significantly reduced than T0, and no difference between PG (35.6 ± 8.2 mm) and CG (33.7 ± 7.3 mm) (p > 0.05) was shown. Similar results were reported one week after surgery (PG: 33.2 ± 14.4 mm; CG: 33.7 ± 13.1 mm; p > 0.05). PG showed significantly lower pain values compared to CG, both at T1 (PG: 3.1 ± 1.5; CG: 4.6 ± 1.8; p = 0.0006) and T2 (PG: 1.0 ± 0.8; CG: 1.9 ± 1.4; p = 0.0063). Conclusion Our results showed that pre-operative low-dose prednisone administration could reduce postoperative sequelae by improving patient comfort after M3M surgery and reducing facial swelling two days and one week after surgical procedures. Trial registration www.clinicaltrials.gov - NCT05830747 retrospectively recorded-Date of registration: 26/04/2023.